О некоторых находках остатков млекопитающих в меловых отложениях Средней Азии - Несов, Л.А. (Вестник зоологии, 1984)
On Some Cretaceous Mammals from the Soviet Middle Asia. Nessov L. A.— Vestn.
zool., 1984, No. 2. Kumsuperus avus gen. et sp. n. (a relatively advanced Eutheria inc.
sed) from the Late Turonian — Conician (Late Cretaceous) of Kizylkum Desert, Uzbek
Soviet Socialist Republic, is described. Talonids M₁₋₂ broad, paraconids of M₂₋₃ small,
placed lingually, M₃ and its talonid somewhat reduced, the whole jaw is high. Bone
iragments of mainmals from Upper Turonian, Upper Cenomanian, (Upper, Cretaceous) and
Upper Albian (Lower Cretaceous) of Kizylkum Desert are also described.